Two new species of Pachyrhynchini from Eastern Luzon, Philippines (Coleoptera, Curculionidae, Entiminae) - Bollino, Maurizio (Zootaxa, 2023)
Metapocyrtus jaysoni Bollino, new species and Apocyrtus tagalog Bollino, new species are described from General Nakar, Quezon, Luzon, Philippines. The male genitalia of each new species including the endophallus is illustrated, as well as that of Apocyrtus auroraensis Rukmane-Bârbale, 2021, and Apocyrtus inflatus Erichson, 1834. In addition, Apocyrtus marinduquensis Rukmane-Bârbale, 2022 is considered a new junior subjective synonym of Apocyrtus auroraensis, of which the type locality is noted as in error.